1996
DOI: 10.1164/ajrccm.154.6.8970360
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation lymphoproliferative disorder in the Epstein-Barr virus-naïve lung transplant recipient.

Abstract: Post-transplantation lymphoproliferative disorder (PTLD) is a widely recognized and often catastrophic complication of organ transplantation. The incidence of PTLD after lung transplantation ranges from 6.2 to 9.4% and is two-fold higher than that seen after organ transplantation of other organs. Primary Epstein-Barr virus (EBV) infection is a major risk factor for PTLD, but the incidence of PTLD in EBV seronegative (EBV-) patients seems to vary with type of organ transplant. The goal of this study was to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
89
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 0 publications
5
89
1
2
Order By: Relevance
“…Secondly, PTLDs in LTx patients appear to occur very early after transplant (median time 7 mo) compared with non-LTx patients (median time, 41 mo), which is consistent with the case in the previous literature (12,23,24,30). In addition, these PTLDs also appear to be clinically aggressive, with 5 of 8 patients dying of their PTLD.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Secondly, PTLDs in LTx patients appear to occur very early after transplant (median time 7 mo) compared with non-LTx patients (median time, 41 mo), which is consistent with the case in the previous literature (12,23,24,30). In addition, these PTLDs also appear to be clinically aggressive, with 5 of 8 patients dying of their PTLD.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of PTLDs appears to depend on several factors, including age, pretransplantation EBV status, immunosuppression regimen, and transplanted organ (5,29,30). The incidence of PTLD in LTx patients varies in the literature from 6 to 10% (12,24). Montone et al (23) reported a very high incidence of 20% that seems to be an outlier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have therefore examined the use of prophylactic antiviral therapy in transplant recipients to reduce the risk of PTLD. Results from studies have been varied, with multiple early studies of anti-viral prophylaxis detecting no impact on PTLD incidence [27,28]. However, one early study was able to detect a reduction in PTLD incidence from 3.9% to 0.5% of SOT recipients who received either acyclovir (administered orally four times daily) or ganciclovir (administered intravenously) while they received highly immunosuppressive antilymphocyte antibody therapy [29].…”
Section: Discussionmentioning
confidence: 99%